Phytolith extraction and counting procedure for modern plant material rich in silica skeletons v2 - Francesca D’Agostini; Javier Ruiz-Pérez; Marco Madella; Vincent Vadez; Carla Lancelotti (2022)
Modern plant tissues are often processed for phytolith analysis. They represent a fundamental source of comparison for archeological and palaeoenvironmental phytolith assemblages; they efficiently serve for morphological studies of phytolith shapes and dimensions and, in the last two decades, they have been increasingly involved in physiological studies, which aim to understand the functioning of Si absorption in plants. Here we present a relatively fast, safe, and inexpensive phytolith extraction, combining a dry ashing technique followed by wet oxidation, and a counting methodology. This protocol offers an optimized strategy that achieves very pure samples, preservation of a high number of silica skeletons (phytoliths in anatomical connection), and a counting method which assures the richness and the evenness of the phytolith assemblage distribution. The methodology described in this paper is optimal for recognition and identification of morphotypes, isotope studies and concentration evaluations. This protocol has been developed to allow researchers to extract phytoliths from modern tissues of leaves, stem and chaff, and it is combined with a new strategy to count phytoliths in slides where several big silica skeletons (>50/100 cells each) are present. References -Andriopoulou, Nafsika C., and Georgios E. Christidis. 2020. ‘Multi-Analytical Characterisation of Wheat Biominerals: Impact of Methods of Extraction on the Mineralogy and Chemistry of Phytoliths’.Archaeological and Anthropological Sciences12 (186).https://doi.org/10.1007/s12520-020-01091-5 -Ball, Terry B. 2016. ‘Morphometric Analysis of Phytoliths: Recommendations towards Standardization from the International Committee for Phytolith Morphometrics’.Journal of Archaeological Science63: 106–11.http://dx.doi.org/10.1016/j.jas.2015.03.023 -Ball, Terry, John S. Gardner, and Jack D. Brotherson. 1996. ‘Identifying Phytoliths Produced by the Inflorescence Bracts of Three Species of Wheat (Triticum MonococcumL.,T. DicocconSchrank., AndT. AestivumL.) Using Computer-Assisted Image and Statistical Analyses’.Journal of Archaeological Science23 (July): 619–32.https://doi.org/10.1006/jasc.1996.0058 -Barboni, Doris, and Laurent Bremond. 2009. ‘Phytoliths of East African Grasses: An Assessment of Their Environmental and Taxonomic Significance Based on Floristic Data’.Review of Palaeobotany and Palynology158: 29–41.https://doi.org/10.1016/j.revpalbo.2009.07.002 -Braune, Caroline, Reinhard Lieberei, Douglas Steinmacher, and Thomas M. Kaiser. 2012. ‘A Simple Microwave Extraction Method for the Isolation and Identification of Plant Opal Phytoliths’.Biologia67 (5): 927–30.https://doi.org/10.2478/s11756-012-0074-1 -Bremond, Laurent, Anne Alexandre, Odile Peyron, and Joël Guiot. 2005. ‘Grass Water Stress Estimated from Phytoliths in West Africa: Grass Water Stress Estimated from Phytoliths’.Journal of Biogeography32: 311–27.https://doi.org/10.1111/j.1365-2699.2004.01162.x -Brochier, Jacques Élie. 2002. ‘Les sédiments anthropiques’.Géologie de la Préhistoire: méthodes, techniques, applications, 453–73. -Cabanes, Dan, Yuval Gadot, Maite Cabanes, Israel Finkelstein, Steve Weiner, and Ruth Shahack-Gross. 2012. ‘Human Impact around Settlement Sites: A Phytolith and Mineralogical Study for Assessing Site Boundaries, Phytolith Preservation, and Implications for Spatial Reconstructions Using Plant Remains’.Journal of Archaeological Science39 (August): 2697–2705.https://doi.org/10.1016/j.jas.2012.04.008 -Cabanes, Dan, Steve Weiner, and Ruth Shahack-Gross. 2011. ‘Stability of Phytoliths in the Archaeological Record: A Dissolution Study of Modern and Fossil Phytoliths’.Journal of Archaeological Science38 (9): 2480–90.https://doi.org/10.1016/j.jas.2011.05.020 -Camargo, Mônica Sartori, Mariana Fernández Honaine, Margarita Osterrieth, Natália Ganzaroli Bozza, Vicente da Mota Silva, Maria Laura Benvenuto, and Marcelo de Almeida Silva.2021. ‘Silicon Fertilization Increases Gas-Exchange and Biomass by Silicophytolith Deposition in the Leaves of Contrasting Drought-Tolerant Sugarcane Cultivars under Well-Watered Conditions’.Plant and Soil.https://doi.org/10.1007/s11104-021-05063-z -Carter, John A. 2009. ‘Atmospheric Carbon Isotope Signatures in Phytolith-Occluded Carbon’.Quaternary International193 (January): 20–29.https://doi.org/10.1016/j.quaint.2007.11.013 -Chen, Iju, Kuang-ti Li, and Cheng-hwa Tsang. 2020. ‘Silicified Bulliform Cells of Poaceae: Morphological Characteristics That Distinguish Subfamilies’.Botanical Studies61 (5).https://doi.org/10.1186/s40529-020-0282-x -Cooke, Julia, and Michelle R. Leishman. 2016. ‘Consistent Alleviation of Abiotic Stress with Silicon Addition: A Meta‐analysis’. Edited by Sue Hartley.Functional Ecology30 (8): 1340–57.https://doi.org/10.1111/1365-2435.12713 -Corbineau, Rémi, Paul E. Reyerson, Anne Alexandre, and Guaciara M. Santos. 2013. ‘Towards Producing Pure Phytolith Concentrates from Plants That Are Suitable for Carbon Isotopic Analysis’.Review of Palaeobotany and Palynology197 (October): 179–85.https://doi.org/10.1016/j.revpalbo.2013.06.001 -Cornelis, Jean‐Thomas, and Bruno Delvaux. 2016. ‘Soil Processes Drive the Biological Silicon Feedback Loop’. Edited by Julia Cooke.Functional Ecology30 (8): 1298–1310.https://doi.org/10.1111/1365-2435.12704 -Coskun, Devrim, Rupesh Deshmukh, Humira Sonah, James G. Menzies, Olivia Reynolds, Jian Feng Ma, Herbert J. Kronzucker, and Richard R. Bélanger. 2019. ‘The Controversies of Silicon’s Role in Plant Biology’.New Phytologist.https://doi.org/10.1111/nph.15343 -Elbaum, Rivka, Cathy Melamed-Bessudo, Noreen Tuross, Avraham A. Levy, and Steve Weiner. 2009. ‘New Methods to Isolate Organic Materials from Silicified Phytoliths Reveal Fragmented Glycoproteins but No DNA’.Quaternary International193 (January): 11–19.https://doi.org/10.1016/j.quaint.2007.07.006 -Elbaum, Rivka, Steve Weiner, Rosa M. Albert, and Michael Elbaum. 2003. ‘Detection of Burning of Plant Materials in the Archaeological Record by Changes in the Refractive Indices of Siliceous Phytoliths’.Journal of Archaeological Science30 (February): 217–26.https://doi.org/10.1006/jasc.2002.0828 -Ermish, Brendan J., and Shannon A. Boomgarden. 2022. ‘Identifying Water Availability with Maize Phytoliths in Range Creek Canyon, Utah’.Journal of Archaeological Science: Reports41.https://doi.org/10.1016/j.jasrep.2021.103267 -Fernández Honaine, Mariana, M. Laura Benvenuto, Lía Montti, Marcela Natal, Natalia L. Borrelli, M. Fernanda Alvarez, Stella Maris Altamirano, Mara De Rito, and Margarita L. Osterrieth.2021. ‘How Are Systematics and Biological and Ecological Features Related to Silica Content in Plants? A Study of Species from Southern South America’.International Journal of Plant Sciences.https://doi.org/10.1086/712357 -Fraysse, Fabrice, Oleg S. Pokrovsky, Jacques Schott, and Jean-Dominique Meunier. 2009. ‘Surface Chemistry and Reactivity of Plant Phytoliths in Aqueous Solutions’.Chemical Geology258: 197–206.https://doi.org/10.1016/j.chemgeo.2008.10.003 -Frick, Daniel A., Rainer Remus, Michael Sommer, Jürgen Augustin, and Friedhelm von Blanckenburg. 2020. ‘Silicon Isotope Fractionation and Uptake Dynamics of Three Crop Plants: Laboratory Studies with Transient Silicon Concentrations’.Biogeosciences.https://doi.org/10.5194/bg-2020-66 -Frick, Daniel A., Jan A. Schuessler, Michael Sommer, and Friedhelm Blanckenburg. 2019. ‘Laser AblationIn SituSilicon Stable Isotope Analysis of Phytoliths’.Geostandards and Geoanalytical Research.https://doi.org/10.1111/ggr.12243 -Gallaher, Timothy J., Sultan Z. Akbar, Phillip C. Klahs, Claire R. Marvet, Ashly M. Senske, Lynn G. Clark, and Caroline A.E. Strömberg. 2020. ‘3D Shape Analysis of Grass Silica Short Cell Phytoliths (GSSCP): A New Method for Fossil Classification and Analysis of Shape Evolution’.New Phytologist.https://doi.org/10.1111/nph.16677 -Ge, Yong, Houyuan Lu, Jianping Zhang, Can Wang, and Xing Gao. 2020. ‘Phytoliths in Inflorescence Bracts: Preliminary Results of an Investigation on Common Panicoideae Plants in China’.Frontiers in Plant Science10.https://doi.org/10.3389/fpls.2019.01736 -Gu, Yansheng, Hongye Liu, Hanlin Wang, Rencheng Li, and Jianxin Yu. 2016. ‘Phytoliths as a Method of Identification for Three Genera of Woody Bamboos (Bambusoideae) in Tropical Southwest China’.Journal of Archaeological Science68: 46–53.https://doi.org/10.1016/j.jas.2015.08.003 -Guerriero, Gea, Ian Stokes, Nathalie Valle, Jean-Francois Hausman, and Christopher Exley. 2020. ‘Visualising Silicon in Plants: Histochemistry, Silica Sculptures and Elemental Imaging’.Cells9.https://doi.org/10.3390/cells9041066 -Hartley, Sue E., Rob N. Fitt, Emma L. McLarnon, and Ruth N. Wade. 2015. ‘Defending the Leaf Surface: Intra- and Inter-Specific Differences in Silicon Deposition in Grasses in Response to Damage and Silicon Supply’.Frontiers in Plant Science6.https://doi.org/10.3389/fpls.2015.00035 -Harvey, Emma L., and Dorian Q Fuller. 2005. ‘Investigating Crop Processing Using Phytolith Analysis: The Example of Rice and Millets’.Journal of Archaeological Science32: 739–52.https://doi.org/10.1016/j.jas.2004.12.010 -Hodson, Martin J. 2019. ‘The Relative Importance of Cell Wall and Lumen Phytoliths in Carbon Sequestration in Soil: A Hypothesis’.Frontiers in Earth Science7 (July): 167.https://doi.org/10.3389/feart.2019.00167 -Hodson, Martin J., Adrian G. Parker, Melanie J. Leng, and Hilary J. Sloane. 2008a. ‘Silicon, Oxygen and Carbon Isotope Composition of Wheat (Triticum Aestivum L.) Phytoliths: Implications for Palaeoecology and Archaeology’.Journal of Quaternary Science23 (4): 331–39.https://doi.org/10.1002/jqs.1176 -Hodson, Martin J.. 2008b. ‘Silicon, Oxygen and Carbon Isotope Composition of Wheat (Triticum Aestivum L.) Phytoliths: Implications for Palaeoecology and Archaeology’.Journal of Quaternary Science23 (4): 331–39.https://doi.org/10.1002/jqs.1176 -Hurtado, Alexander Calero, Denise Aparecida Chiconato, Renato de Mello Prado, Gilmar da Silveira Sousa Junior, Dilier Olivera Viciedo, Yanery Pérez Díaz, Kolima Peña Calzada, and Priscila Lupino Gratão.2020. ‘Silicon Alleviates Sodium Toxicity in Sorghum and Sunflower Plants by Enhancing Ionic Homeostasis in Roots and Shoots and Increasing Dry Matter Accumulation’.Silicon.https://doi.org/10.1007/s12633-020-00449-7 -Jadhao, Kundansing Rajpalsing, and Gyana Ranjan Rout. 2020. ‘Silicon (Si) Enhances the Resistance in Finger Millet Genotypes against Blast Disease’.Journal of Plant Pathology.https://doi.org/10.1007/s42161-020-00622-2 -Jenkins, Emma. 2009. ‘Phytolith Taphonomy: A Comparison of Dry Ashing and Acid Extraction on the Breakdown of Conjoined Phytoliths Formed in Triticum Durum’.Journal of Archaeological Science36 (October): 2402–7.https://doi.org/10.1016/j.jas.2009.06.028 -Jenkins, Emma, Khalil Jamjoum, Sameeh Nuimat, Richard Stafford, Stephen Nortcliff, and Steven Mithen. 2016. ‘Identifying Ancient Water Availability through Phytolith Analysis: An Experimental Approach’.Journal of Archaeological Science73: 82–93.https://doi.org/10.1016/j.jas.2016.07.006 -Jenkins, Emma, Lea Predanich, Sameeh Nuimat, Khalil Jamjoum, and Richard Stafford. 2020. ‘Assessing Past Water Availability Using Phytoliths Fro the C4 Plant Sorghum Bicolor: An Experimental Approah’.Journal of Archaeological Science33.https://doi.org/10.1016/j.jasrep.2020.102460. -Jones, L.H.P., Milne, A.A. Studies of silica in the oat plant.Plant Soil18,207–220 (1963).https://doi.org/10.1007/BF01347875 -Karoune, E., 2020. Pre-print of Assessing Open Science Practices in Phytolith Research (preprint). Open Science Framework.https://doi.org/10.31219/osf.io/fa7q3 -Kameník, J., J. Mizera, and Z. Řanda. 2013. ‘Chemical Composition of Plant Silica Phytoliths’.Environmental Chemistry Letters11 (June): 189–95.https://doi.org/10.1007/s10311-012-0396-9 -Katz, Ofir, Dan Cabanes, Stephen Weiner, Aren M. Maeir, Elisabetta Boaretto, and Ruth Shahack-Gross. 2010. ‘Rapid Phytolith Extraction for Analysis of Phytolith Concentrations and Assemblages during an Excavation: An Application at Tell Es-Safi/Gath, Israel’.Journal of Archaeological Science37 (July): 1557–63.https://doi.org/10.1016/j.jas.2010.01.016 -Ksiaa, Mariem, Nèjia Farhat, Mokded Rabhi, Amine Elkhouni, Abderrazak Smaoui, Ahmed Debez, Cécile Cabassa-Hourton, Arnould Savouré, Chedly Abdelly, and Walid Zorrig. 2021. ‘Silicon (Si) Alleviates Iron Deficiency Effects in Sea Barley (Hordeum Marinum) by Enhancing Iron Accumulation and Photosystem Activities’.Silicon, October.https://doi.org/10.1007/s12633-021-01376-x -Kumar, Santosh, Yonat Milstein, Yaniv Brami, Michael Elbaum, and Rivka Elbaum. 2017. ‘Mechanism of Silica Deposition in Sorghum Silica Cells’.New Phytologist213: 791–98. https://doi.org/10.1111/nph.14173 -Kumar, Santosh, Milan Soukup, and Rivka Elbaum. 2017. ‘Silicification in Grasses: Variation between Different Cell Types’.Frontiers in Plant Science8 (March).https://doi.org/10.3389/fpls.2017.00438 -Leng, Melanie J., George E. A. Swann, Martin J. Hodson, Jonathan J. Tyler, Siddharth V. Patwardhan, and Hilary J. Sloane. 2009. ‘The Potential Use of Silicon Isotope Composition of Biogenic Silica as a Proxy for Environmental Change’.Silicon, 65–77.https://doi.org/10.1007/s12633-009-9014-2 -Lombardo, U., Ruiz-Pérez, J., Rodrigues, L., Mestrot, A., Mayle, F., Madella, M., Szidat, S., Veit, H., 2019.Holocene land cover change in south-western Amazonia inferred from paleoflood archives. Global and Planetary Change 174, 105–114.https://doi.org/10.1016/j.gloplacha.2019.01.008 -Lux, Alexander, Miroslava Luxova, Taiichiro Hattori, Shinobu Inanaga, and Yukihiro Sugimoto. 2002. ‘Silicification in Sorghum (Sorghum Bicolor) Cultivars with Different Drought Tolerance’.Physiologia Plantarum115 (May): 87–92.https://doi.org/10.1034/j.1399-3054.2002.1150110.x -Lv, Wanjie, Guomo Zhou, Guangsheng Chen, Yufeng Zhou, Zhipeng Ge, Zhengwen Niu, Lin Xu, and Yongjun Shi. 2020. ‘Effects of Different Management Practices on the Increase in Phytolith-Occluded Carbon in Moso Bamboo Forests’.Frontiers in Plant Science11.https://doi.org/10.3389/fpls.2020.591852 -Ma, Jian Feng, Kazunori Tamai, Naoki Yamaji, Namiki Mitani, Saeko Konishi, Maki Katsuhara, Masaji Ishiguro, Yoshiko Murata, and Masahiro Yano. 2006. ‘A Silicon Transporter in Rice’.Nature440 (March): 688–91.https://doi.org/10.1038/nature04590 -Ma, Jian Feng, and Naoki Yamaji. 2006. ‘Silicon Uptake and Accumulation in Higher Plants’.Trends in Plant Science11 (8): 392–97.https://doi.org/10.1016/j.tplants.2006.06.007 -Ma. 2015. ‘A Cooperative System of Silicon Transport in Plants’.Trends in Plant Science20 (7): 435–42.https://doi.org/10.1016/j.tplants.2015.04.007 -Madella, M., M.K. Jones, P. Echlin, A. Powers-Jones, and M. Moore. 2009. ‘Plant Water Availability and Analytical Microscopy of Phytoliths: Implications for Ancient Irrigation in Arid Zones’.Quaternary International193 (1–2): 32–40.https://doi.org/10.1016/j.quaint.2007.06.012 -Madella, M., A.H. Powers-Jones, and M.K. Jones. 1998. ‘A Simple Method of Extraction of Opal Phytoliths from Sediments Using a Non-Toxic Heavy Liquid’.Journal of Archaeological Science25 (8): 801–3.https://doi.org/10.1006/jasc.1997.0226 -Madella, Marco, and Carla Lancelotti. 2012. ‘Taphonomy and Phytoliths: A User Manual’.Quaternary International275 (October): 76–83.https://doi.org/10.1016/j.quaint.2011.09.008 -Madella, Marco, Carla Lancelotti, and Juan José García-Granero. 2016. ‘Millet Microremains—an Alternative Approach to Understand Cultivation and Use of Critical Crops in Prehistory’.Archaeological and Anthropological Sciences8: 17–28.https://doi.org/10.1007/s12520-013-0130-y -Markovich, Oshry, Santosh Kumar, Dikla Cohen, Sefi Addadi, Eyal Fridman, and Rivka Elbaum. 2019. ‘Silicification in Leaves of Sorghum Mutant with Low Silicon Accumulation’.Silicon11: 2385–91.https://doi.org/10.1007/s12633-015-9348-x Markovich, Oshry, Nerya Zexer, Boaz Negin, Yotam Zait, Shula Blum, Alon Ben-Gal, and Rivka RivkaElbaum. 2022. ‘Low Si Combined with Drought Causes Reduced Transpiration in Sorghum Lsi1 Mutant’.Plant and Soil, February.https://doi.org/10.1007/s11104-022-05298-4 -Mateos-Naranjo, Enrique, Luis Andrades-Moreno, and Anthony J. Davy. 2013. ‘Silicon Alleviates Deleterious Effects of High Salinity on the Halophytic Grass Spartina Densiflora’.Plant Physiology and Biochemistry63 (February): 115–21.https://doi.org/10.1016/j.plaphy.2012.11.015 -Miller Rosen, Arlene. 1994. ‘Identifying Ancient Irrigation: A New Method Using Opaline Phytoliths from Emmer Wheat’.Journal of Archaeological Science21: 125–32. -Mitani, N. 2005. ‘Uptake System of Silicon in Different Plant Species’.Journal of Experimental Botany56 (414): 1255–61.https://doi.org/10.1093/jxb/eri121 -Ngoc Nguyen, Minh, Stefan Dultz, and Georg Guggenberger. 2014. ‘Effects of Pretreatment and Solution Chemistry on Solubility of Rice‐straw Phytoliths’.Journal of Plant Nutrition and Soil Science177 (June): 349–59.https://doi.org/10.1002/jpln.201300056 -Parr, Jeff F. 2006. ‘Effect of Fire on Phytolith Coloration’.Geoarchaeology21 (2): 171–85.https://doi.org/10.1002/gea.20102 -Parr, Jeffrey F., and Leigh A. Sullivan. 2014. ‘Comparison of Two Methods for the Isolation of Phytolith Occluded Carbon from Plant Material’.Plant and Soil374: 45–53.https://doi.org/10.1007/s11104-013-1847-1 -Parr, J.F., V. Dolic, G. Lancaster, and W.E. Boyd. 2001. ‘A Microwave Digestion Method for the Extraction of Phytoliths from Herbarium Specimens’.Review of Palaeobotany and Palynology116: 203–12.https://doi.org/10.1016/S0034-6667(01)00089-6 -Pearsall, Deborah M. 2016.Paleoethnobotany- A Handbook of Procedures. 3rd ed. Oxford: Routledge Taylor & Francis Group. -Piperno, Dolores R. 2006.Phytoliths. Oxford: Altamira press. -Prentice, Andrea J., and Elizabeth A. Webb. 2016. ‘The Effect of Progressive Dissolution on the Oxygen and Silicon Isotope Composition of Opal-A Phytoliths: Implications for Palaeoenvironmental Reconstruction’.Palaeogeography, Palaeoclimatology, Palaeoecology453: 42–51.https://doi.org/10.1016/j.palaeo.2016.03.031 -Roy, Biswajit, Sutapa Patra, and Prasanta Sanyal. 2020. ‘The Carbon Isotopic Composition of Occluded Carbon in Phytoliths: A Comparative Study of Phytolith Extraction Methods’.Review of Palaeobotany and Palynology.https://doi.org/10.1016/j.revpalbo.2020.104280 -Rudall, Paula J., Christina J. Prychid, and Thomas Gregory. 2014. ‘Epidermal Patterning and Silica Phytoliths in Grasses: An Evolutionary History’.The Botanical Review80 (March): 59–71.https://doi.org/10.1007/s12229-014-9133-3 -Santos, Guaciara M, Anne Alexandre, Heloisa H G Coe, Paul E Reyerson, John R Southon, and Cacilda N De Carvalho. 2010. ‘The Phytolith14C Puzzle: A Tale of Background Determinations and Accuracy Tests’.Radiocarbon52 (1): 113–28.https://doi.org/10.1017/S0033822200045070 -Schulz-Kornas, Ellen, Caroline Braune, Daniela E. Winkler, and Thomas M. Kaiser. 2017. ‘Does Silica Concentration and Phytolith Ultrastructure Relate to Phytolith Hardness?’Biosurface and Biotribology3: 135–43.https://doi.org/10.1016/j.bsbt.2017.12.004 -Shahack-Gross, Ruth, Aldo Shemesh, Dan Yakir, and Steve Weiner. 1996. ‘Oxygen Isotopic Composition of Opaline Phytoliths: Potential for Terrestrial Climatic Reconstruction’.Geochimica et Cosmochimica Acta60 (20): 3949–53.https://doi.org/10.1016/0016-7037(96)00237-2 -Stamm, Franziska M., Merlin Méheut, Thomas Zambardi, Jérôme Chmeleff, Jacques Schott, and Eric H. Oelkers. 2020. ‘Extreme Silicon Isotope Fractionation Due to Si Organic Complexation: Implications for Silica Biomineralization’.Earth and Planetary Science Letters541.https://doi.org/10.1016/j.epsl.2020.116287 -Strömberg, Caroline A. E., Verónica S. Di Stilio, and Zhaoliang Song. 2016.‘Functions of Phytoliths in Vascular Plants: An Evolutionary Perspective’. Edited by Jane De Gabriel.Functional Ecology30: 1286–97.https://doi.org/10.1111/1365-2435.12692 -Strömberg, Caroline A.E. 2009. ‘Methodological Concerns for Analysis of Phytolith Assemblages: Does Count Size Matter?’Quaternary International193: 124–40.https://doi.org/10.1016/j.quaint.2007.11.008 Twiss, P. C., Erwin Suess, and R. M. Smith. 1969. ‘Morphological Classification of Grass Phytoliths’.Soil Science Society of America Journal33: 109–15.https://doi.org/10.2136/sssaj1969.03615995003300010030x -Tyler, Jonathan J., Melanie J. Leng, and Hilary J. Sloane. 2007. ‘The Effects of Organic Removal Treatment on the Integrity of Δ18O Measurements from Biogenic Silica’.Journal of Paleolimnology37 (May): 491–97.https://doi.org/10.1007/s10933-006-9030-9 -Vatansever, Recep, Ibrahim Ilker Ozyigit, Ertugrul Filiz, and Nermin Gozukara. 2017. ‘Genome-Wide Exploration of Silicon (Si) Transporter Genes, Lsi1 and Lsi2 in Plants; Insights into Si-Accumulation Status/Capacity of Plants’.BioMetals30: 185–200.https://doi.org/10.1007/s10534-017-9992-2 -Watling, Kym M., Jeff F. Parr, Llew Rintoul, Christopher L. Brown, and Leigh A. Sullivan. 2011. ‘Raman, Infrared and XPS Study of Bamboo Phytoliths after Chemical Digestion’.Spectrochimica Acta Part A: Molecular and Biomolecular Spectroscopy80 (October): 106–11.https://doi.org/10.1016/j.saa.2011.03.002 -Webb, Elizabeth A., and Fred J. Longstaffe. 2002. ‘Climatic Influences on the Oxygen Isotopic Composition of Biogenic Silica in Prairie Grass’.Geochimica et Cosmochimica Acta66 (11): 1891–1904.https://doi.org/10.1016/S0016-7037(02)00822-0 Webb, Elizabeth A. 2010. ‘Limitations on the Climatic and Ecological Signals Provided by the Δ13C Values of Phytoliths from a C4 North American Prairie Grass’.Geochimica et Cosmochimica Acta74 (June): 3041–50.https://doi.org/10.1016/j.gca.2010.03.006 -Yang, Shilei, Qian Hao, Hailong Wang, Lukas Van Zwieten, Changxun Yu, Taoze Liu, Xiaomin Yang, Xiaodong Zhang, and Zhaoliang Song. 2020.‘A Review of Carbon Isotopes of Phytoliths: Implications for Phytolith-Occluded Carbon Sources’.Journal of Soils and Sediments.https://doi.org/10.1007/s11368-019-02548-4 -Zancajo, Victor M. R., Sabrina Diehn, Nurit Filiba, Gil Goobes, Janina Kneipp, and Rivka Elbaum. 2019. ‘Spectroscopic Discrimination of Sorghum Silica Phytoliths’.Frontiers in Plant Science10.https://doi.org/10.3389/fpls.2019.01571 -Zurro, Debora. 2018. ‘One, Two, Three Phytoliths: Assessing the Minimum Phytolith Sum for Archaeological Studies’.Archaeological and Anthropological Sciences10 (October): 1673–91.https://doi.org/10.1007/s12520-017-0479-4 -Zurro, Débora, Juan José García-Granero, Carla Lancelotti, and Marco Madella. 2016. ‘Directions in Current and Future Phytolith Research’.Journal of Archaeological Science68 (April): 112–17.https://doi.org/10.1016/j.jas.2015.11.014